Feasibility of radiation dose range capable to cause subacute course of radiation syndrome - Krasnyuk V.I.; Ustyugova А.А. (Саратовский научно-медицинский журнал, 2013)
There had been analysed cases of radiation syndrome which clinical picture takes an intermediate place between the acute radiation syndrome (ARS) and the chronic radiation syndrome (CRS), and differs from them because of a subacute. This variant of disease can develop as a result of the fractioned or prolonged radiation lasting from several days to several weeks. Development of primary reaction took place only in the extremely hard cases which ends with an early fatality. After the general radiation the marrow failure was characterized by directly expressed formation and restoration period, specific features of which were defined by the radiation duration, a total dose and dose derivative. The most typical outcomes of a subacute radiation syndrome are death from infectious complications in the period of an eruptive phase or leukosis development in the remote period.